Entrepreneurship Education and Community Empowerment in Islamic Boarding School: Lessons from a Sustainable Sheep Farming Initiative - Galih Eko Dwi Prastowo; Sri Nurhayati; Wedi Fitriana (Jurnal Ilmiah Profesi Pendidikan, 2025)
This study explores the impact of entrepreneurship education within Islamic boarding schools (pesantren) on rural community empowerment in Indonesia, focusing on a sheep farming initiative at Pesantren Persis 16 Cipada in West Java. Traditionally serving as centers for Islamic learning and moral development, pesantren have evolved to address the socioeconomic needs of their communities by integrating vocational training and entrepreneurship into their curricula. Employing a qualitative case study approach, data were collected over three months through semi-structured interviews with program participants—including the program manager, a tutor, and five local residents—participant observation, and document analysis. Findings are categorized into three main themes: (1) Entrepreneurship Education and Economic Empowerment—the program provided participants with practical skills in sheep farming and business management, leading to increased economic independence and a reported 30% rise in household income for some participants; (2) Community Collaboration and Engagement—the initiative fostered unity and collective responsibility, enhancing social cohesion through shared decision-making and mutual support; and (3) Challenges in Sustaining the Initiative—issues such as limited funding, environmental factors affecting livestock health, and restricted market access posed threats to the program's sustainability. The study concludes that entrepreneurship education within pesantren can significantly contribute to rural economic empowerment and community development. By combining practical skills training with religious education, institutions like Pesantren Persis 16 Cipada effectively address both spiritual and economic needs, promoting resilience and sustainable development. However, to maximize their impact, these initiatives require additional support to overcome challenges related to financial resources, environmental adaptation, and market expansion. The findings highlight the potential of faith-based educational institutions to act as agents of social and economic change in rural settings.